Diversity of Pathogenic Fungi and Disease on Vegetable Crops at Polyculture Systems - Eddy Tri Sucianto; Muachiroh Abbas (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Vegetables polyculture system is potentially increasing pathogenic fungi diversity because various plant hosts are available. There is no data about patogenic fungi diversity at polyculture vegetable farming in Serang village, District of Karangreja, Purbalingga Regency. This study aimed to determine patogenic fungal diversity and disease percentage caused by the fungi at polyculture vegetable farming in Serang village, District of Karangreja, Purbalingga Regency. This research used purposive random sampling. Infected plants were collected at ten polyculture farming locations and fungal identification was performed at the laboratory. Fungi were identified morphologically based on the signs, symptoms, as well as macroscopic and microscopic characters. The fungi's pathogenity was determined by applying Koch's postulate test. The data were analyzed descriptively through literature comparison. The results showed that seven fungal species were found at polyculture farms in Serang Village. The obtained fungi were Colletotrichum sp., Fusarium sp., Alternaria sp., Septoria sp., Cercospora sp., Botryodiplodia sp., and Nigrospora sp. The lowest damage was 18.24% on tomato fruit infected by Fusarium sp. and the highest was on chili plants which was caused by Colletotrichum sp. The data is the first report for polycuture system. The obtained data has important implication for the management of vegetables farming in Serang Village.